DINAMIKA KEPERCAYAAN PUBLIK TERHADAP LEMBAGA ANTI KORUPSI: STUDI KASUS DUGAAN PEMERASAN OLEH MANTAN KETUA KPK FIRLI BAHURI - Firmansyah, Rizki; Harahap, Chisa Belinda (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Corruption in Indonesia has been a systemic problem that has developed since the time of the Nusantara kingdoms and continues into the modern era of government. The Corruption Eradication Commission (KPK) has a very important role in eradicating and preventing corruption through its authority to investigate, prosecute, and monitor corruption. However, the case involving KPK Chairman Firli Bahuri in the extortion of former Agriculture Minister Syahrul Yasin Limpo raises serious questions about the integrity of the institution he leads. Firli's designation as a suspect in this case highlights a potential conflict of interest and damages the KPK's reputation as an anti-corruption agency. This article analyzes the link between KPK's duties and legal cases involving its top leadership, and the impact on the agency's credibility and effectiveness in fighting corruption. It finds that public distrust of the KPK has increased due to Firli's involvement in the extortion case, which requires an evaluation and strengthening of the internal control system to restore public confidence in the institution.